Edukasi Pemanfaatan Herbal (Daun Sirih, Cengkeh dan Kayu Manis) Sebagai Obat Kumur Untuk Mencegah Caries Gigi Di Kawasan Gelandangan Chow Kit Malaysia - Aryantini, Dyah; Shofi, Muh.; Agustina, Lia; Yuliati, Ninis; Fauzi Sabban, Indra (Fakultas Pertania Universitas Muara Bungo, 2026)
The Chow Kit settlement in Kuala Lumpur, Malaysia, is characterized by a population of homeless and low-to-no-income residents. As such, this area frequently becomes a focus for social institutions implementing Community Service Responsibility (CSR) programs, particularly in the health domain. This CSR initiative represents a collaborative effort between USIM Malaysia (Faculty of Dentistry) and the Faculty of Pharmacy (IIK Bhakti Wiyata Kediri, Indonesia), focusing on educational interventions to prevent and reduce dental caries through the use of herbal mouthwash formulations. Dental caries has emerged as a prevalent oral health concern with a significant impact on overall health. The condition originates from the formation of Streptococcus mutans bacterial biofilms, which are typically exacerbated by excessive consumption of sugary foods and tobacco use. The community service methodology employed participatory counseling and educational approaches, utilizing purposive sampling techniques. Evaluation of the program demonstrated enhanced comprehension among the 22 participants, with mean pre-test scores of 57.39 improving to 79.09 post-intervention, reflecting a 21.7% increase. While some participants maintained baseline scores, 86.5% of attendees (19 individuals) achieved improvements exceeding 20 points. Sustainable monitoring and evaluation mechanisms remain essential, given that the participant cohort primarily consists of homeless individuals whose transient living circumstances often preclude consistent maintenance of personal oral hygiene practices.